Mothers' distress exposure and children's withdrawn behavior – A moderating role for the Interferon Gamma Gene (IFNG) - Pinto, R.; Belsky, J.; Baptista, J.; Carvalho-Correia, E.; Cunha, J. P.; Soares, I.; Mesquita, A. R. (Developmental Psychobiology, 2020)
The dysregulation of the inflammatory response, including pro‐inflammatory molecules, produces neuropsychiatric symptoms and depression‐like behavior, including withdrawal from the physical and social environment. Genetic variants that enhance immune reactivity may thus increase inflammatory and withdrawn reactions to stress. Here we investigated a functional polymorphism of Interferon Gamma gene (IFNG +874 T > A, rs2430561) as moderator of the relationship between mothers’ distress exposure and children's withdrawn behavior at preschool age. Participants were 198 Portuguese preschool children (mean age = 57.98 months). Exposure to mother's distress was assessed using the Brief Symptom Inventory, and withdrawn behavior with the Caregiver Teacher Report Form. All children provided saliva samples for genotyping. Contrary to expectations based on prior work, the rs2430561 AA genotype—not the T variant—interacted with (high levels of) mothers’ distress exposure, to increase children's withdrawn behavior. No significant main effects were detected. The polymorphism in Interferon Gamma gene showed specific environmental stressor‐dependent effects on withdrawn behavior during childhood, ones which are interpreted in light of the "behavioral immune system" hypothesis, and which proved inconsistent with diathesis‐stress thinking.